The Survey Research of Student Perception on The Use of Edmodo as a Learning Platform in Academic Listening Class. - Betari Utama Safitri (Retain: Journal of Research in English Language Teaching, 2025)
Listening skill has become major problem to master in Indonesia. To accommodate students learning, teachers are encouraged to use technology as media in teaching listening. The media that used in this study is Edmodo. This study have purpose to proof Edmodo as an effective learning media and a media that able to help student in their listening skills. This study used a quantitative approach in the form of survey research and questionnaires are used to collect the data. The result of this study may differ with the other study that have been conducted. Students have different perceptions and opinions toward Edmodo that used in the Academic Listening Course.